Evaluation of pediatric vision screening and digital referral routines in an interprofessional setting in Norway - Horgen, Gro; Hummelen, Marlies; Strasser, Eva; Svarverud, Ellen; Sten, Lotte-Guri Bogfjellmo (Scandinavian Journal of Optometry and Visual Science, 2024)
Vision is crucial for childhood development, and ensuring good vision in children is one of the United Nation’s sustainability goals. Most countries have a childhood vision screening programme, and in Norway screening in children aged 4–5 years is performed in community health centres (CHC). Specialist health services such as ophthalmology and/or orthoptics are the referral bodies. However, access to these may be limited and they may be a long distance away from the child’s home, while optometrists are often more available and accessible. This study aims to investigate if vision screening reliably detects vision problems and to explore if using paediatric optometry as a referral body can relieve the specialist health services. The study also aims to report frequency of refractive errors and management of vision problems in this age group. Of 274 children who attended vision screening by school nurses at the CHC in Kongsberg, Norway, parents of 213 (77.7%) consented to a separate eye and vision examination by a paediatric optometrist. Agreements in screening results between school nurses and the paediatric optometrists were evaluated. Separately, an ophthalmologist and an orthoptist assessed records from the eye examinations through a digital communication tool (Eyecheck System AS). Agreements in diagnoses and management decisions between optometrists and the specialist health services were evaluated. Amblyopia or ocular pathology was found in 1.9% of the children, which were all identified by the vision screening. The vision screening had a sensitivity and specificity of 62.3% and 58.6%, respectively, for detecting other vision problems in need of treatment or follow-up. Hypermetropia was present in 82.7% of the children (58.0% low, 18.5% moderate, 6.5% high hypermetropia), 16.4% had emmetropia and 1.0% had myopia. Glasses were prescribed to 8.5% of the children and 16.4% were scheduled for follow-ups. There was a high level of agreement in management between optometrists and specialists (ophthalmologist 80.3%, orthoptist 81.7%). The vision screening reliably detected amblyopia and ocular pathology, and most refractive errors were detected. The high degree of agreement between the three eye care professions suggests that paediatric optometrists can be used as the referral body for this age group. Availability of a digital communication tool provides support for the paediatric optometrists in their decision making and can help relieve the specialist health services by providing children with an eye examination and vision correction earlier and more easily.